Analisis Peredaran Rokok Illegal Di Wilayah Kabupaten Cianjur - Cecep Wiharma; M. Rendi Aridhayandi; Ismail Muhammad (Intellectual Law Review (ILRE), 2023)
Illegal cigarettes are increasingly circulating in the community, the cheaper price is certainly a driving factor for the increasingly active smuggling of illegal cigarettes. The public welcomes the existence of illegal cigarettes, because for consumers today is a declining economy. Identification of the problem in the study of how the impact of the widespread circulation of illegal cigarettes in Cianjur Regency, this research method uses Juridical Normative Law, a descriptive approach that can be used to understand the problems raised by researchers related to the Criminal Case of Illegal Cigarette Circulation. The researcher uses a descriptive type of researcher with a juridical normative approach. The results of the research on the impact of the circulation of illegal cigarettes without excise, the state suffered high losses. With the circulation of cigarettes without excise, the state suffered losses of tens of billions and even trillions of rupiah. The Cianjur District Police and Satpol PP conducted raid operations on markets and found hundreds of packs of illegal cigarettes. Some time ago together with Satpol PP held raids on illegal cigarettes, it turned out that they were found in several stalls or kiosks of traders, after socialization with sources directly from Customs and Excise residents.